The Politics of Identity Emerging Indigeneity - Harris, Michelle; Nakata, Martin; Carlson, Bronwyn (UTS ePRESS, 2013)
The issue of Indigenous identity has gained more attention in recent years from social science scholars, yet much of the discussions still centre on the politics of belonging or not belonging. While these recent discussions in part speak to the complicated and contested nature of Indigeneity, both those who claim Indigenous identity and those who write about it seem to fall into a paradox of acknowledging its complexity on the one hand, while on the other hand reifying notions of 'tradition' and 'authentic cultural expression' as core features of an Indigenous identity. Since identity theorists generally agree that who we understand ourselves to be is as much a function of the time and place in which we live as it is about who we and others say we are, this scholarship does not progress our knowledge on the contemporary characteristics of Indigenous identity formations. The range of international scholars in this volume have begun an approach to the contemporary identity issues from very different perspectives, although collectively they all push the boundaries of the scholarship that relate to identities of Indigenous people in various contexts from around the world. Their essays provide at times provocative insights as the authors write about their own experiences and as they seek to answer the hard questions: Are emergent identities newly constructed identities that emerge as a function of historical moments, places, and social forces? If so, what is it that helps to forge these identities and what helps them to retain markers of Indigeneity? And what are some of the challenges (both from outside and within groups) that Indigenous individuals face as they negotiate the line between 'authentic' cultural expression and emergent identities? Is there anything to be learned from the ways in which these identities are performed throughout the world among Indigenous groups? Indeed why do we assume claims to multiple racial or ethnic identities limits one's Indigenous identity? The question at the heart of our enquiry about the emerging Indigenous identities is when is it the right time to say me, us, we... them?